Pelatihan penyusunan anggaran komprehensip pada pemilik usaha gerabah di Kecamatan Pattallassang Kabupaten Takalar - Anwar Anwar; Zainal Ruma; Hety Budiyanti (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) is a Pottery micro-small business. Business partners are still traditionally managed without good calculations or estimates in the budgeting. Equipping business owners with this knowledge will greatly assist the development of their professionalism in business management. The purpose of this activity is to motivate pottery business owners to have the knowledge and skills to be able to make a comprehensive budget preparation as a prerequisite in developing their business. This activity used a combination of lecture and practice methods. Participants consisted of pottery business owners in Pattallassang District, Takalar Regency. The results achieved from this activity are (1) Pottery business owners are familiar with the elements in the preparation of the budget, (2) able to record sales as a basis for future sales projections, (3) already know the systematic comprehensive budget preparation. The limitation in this training is that the implementation method has not used the technical assistance, so that knowledge about comprehensive budget preparation can be implemented in business activities.